Chymase Level in Dengue Virus Infection With or Without Positive Non-Structural 1(NS1) - Kasiyati, Menik; Nugraha, Jusak; Kahar, Hartono (Jurnal Teknologi Laboratorium, 2019)
Thrombocytopenia, leukopenia, and monocytosis are laboratory parameters in the diagnosis of dengue virus infection. In addition to monocyte cells, mast cells also play a role in the innate immune response, where degranulation of mast cells will occur, which will secretion the active vaso mediator, Chymase. Chymase has a role in increasing vascular permeability resulting in plasma leakage in patients with dengue virus infection to determine the number of platelets, leukocytes, monocytes and chymase levels in patients with dengue infection in the acute phase. The platelet count mean in NS1 (+) was 132,140 cells / mm3 and the platelet count in the NS1 group was (-) 176,000 cells / mm3. The mean leukocytes NS1 (+) showed results of 4,350 cells / mm3 and NS1 (-) 5,250 cells / mm3. The mean monocyte NS1 (+) monocyte count was 8.26%, and NS1 (-) group was 8.76%. There were no significant differences in platelet counts, leukocytes and monocytes between NS1 (+) and NS1 (-) (P value> 0.05). The mean Chymase NS1 (+) 23.48, NS1 (-) 23.05 ng / mL and the control group 1.47ng / mL.